IMMU-08. PHASE I TRIAL (NCT02457845) SAFETY, TOLERABILITY AND PRELIMINARY EFFICACY OF IMMUNOVIROTHERAPY WITH HSV G207 IN CHILDREN WITH PROGRESSIVE MALIGNANT SUPRATENTORIAL BRAIN TUMORS. Issue 2 (22nd June 2018) - Friedman, Gregory; Bag, Asim; Madan-Swain, Avi; Li, Rong; Kachurak, Kara; Osorio, Diana; Hukin, Juliette; Martin, Allison; Pastakia, Devang; Karajannis, Matthias; Bernstock, Joshua; Fiveash, John; et al.
Abstract: BACKGROUND: Outcomes for children with progressive malignant supratentorial brain tumors are dismal. Preclinical evidence indicates that pediatric brain tumors are highly sensitive to genetically engineered oncolytic HSV-1 G207, which lacks genes essential for replication in normal brain. We report on this first-in-children oncolytic virotherapy brain tumor trial of G207. DESIGN/METHODS: A 3 + 3 design was used to evaluate the safety, tolerability and preliminary efficacy of G207 at two doses (10 7 and 10 8 plaque-forming units). After informed consent, patients underwent biopsy to confirm viable tumor followed by placement of up to four silastic intratumoral catheters. The following day, G207 was infused by convection enhanced delivery over 6 hours. Patients were assessed for viral shedding and viremia by PCR and response by serial MRIs. RESULTS: Six subjects have been treated (5 glioblastoma; 1 anaplastic astrocytoma). No dose limiting toxicities, serious adverse events, or ≥ grade 2 toxicities related to G207 have occurred. No G207 shedding or viremia was detected in the saliva, conjunctiva or blood at any time. Evidence of radiographic responses to G207 were seen in 5 of 6 patients including a patient >12 months post-G207 with an ongoing response and improvement in performance score from 80 to 100. CONCLUSION: G207 delivered intratumorally is safe and tolerable in children with progressive malignant supratentorial brain tumors. Preliminary evidence of efficacy is very promising to date. The next phase of the study (NCT02457845) will test the safety of G207 combined with a single 5 Gy dose of radiation within 24 hours of virus inoculation.